Antiproliferative and Apoptosis-Inducing Activities of 4-Isopropyl-2, 6-bis(1-phenylethyl)phenol Isolated from Butanol Fraction of Cordyceps bassiana. (2nd April 2015) - Kim, Ji Hye; Lee, Yunmi; Sung, Gi-Ho; Kim, Han Gyung; Jeong, Deok; Park, Jae Gwang; Baek, Kwang-Soo; Sung, Nak Yoon; Yang, Sungjae; Yoon, Deok Hyo; Lee, Sang Yeol; Kang, Hyojeung; et al.
Abstract : The Cordyceps species have been widely used for treating various cancer diseases. Although the Cordyceps species have been widely known as an alternative anticancer remedy, which compounds are responsible for their anticancer activity is not fully understood. In this study, therefore, we examined the anticancer activity of 5 isolated compounds derived from the butanol fraction (Cb-BF) of Cordyceps bassiana . For this purpose, several cancer cell lines such as C6 glioma, MDA-MB-231, and A549 cells were employed and details of anticancer mechanism were further investigated. Of 5 compounds isolated by activity-guided fractionation from BF of Cb-EE, KTH-13, and 4-isopropyl-2, 6-bis(1-phenylethyl)phenol, Cb-BF was found to be the most potent antiproliferative inhibitor of C6 glioma and MDA-MB-231 cell growth. KTH-13 treatment increased DNA laddering, upregulated the level of Annexin V positive cells, and altered morphological changes of C6 glioma and MDA-MB-231 cells. In addition, KTH-13 increased the levels of caspase 3, caspase 7, and caspase 9 cleaved forms as well as the protein level of Bax but not Bcl-2. It was also found that the phosphorylation of AKT and p85/PI3K was also clearly reduced by KTH-13 exposure. Therefore, our results suggest KTH-13 can act as a potent antiproliferative and apoptosis-inducing component from Cordyceps bassiana, contributing to the anticancer activity of this mushroom.